(untitled) (American Journal of Islam and Society, 2014)
When writing about Islamic sectarian diversity, the vast majority of authors pay attention only to Sunni and Shi‘i Islam. Yet there exists a third group drawn from the earliest conflicts that rent the Muslim ummah apart: the Ibadis. If they are mentioned at all, it is usually little more than a footnote remarking that this group is the remnant of the Khariji secession in 657. Yet this third group – today predominant in Oman and Zanzibar, with populations also in Algeria, Libya, and Tunisia – played an important political and theological role in the immediate post-Prophetic period. Due to this word’s negative connotation, however, Ibadis do not refer to themselves as Kharijis, a group historically viewed as religious extremists by other Muslims. Instead, “Ibadi” comes from the enigmatic Abdullah ibn Ibad/Abad who died early in the eighth century, although, as the author notes, it is likely that his successor Jabir ibn Zayd played a more important role in founding the group. Addressing the dearth of English-language resources on Ibadi beliefs, Valerie J. Hoffman has written The Essentials of Ibāḍī Islam in “an attempt to introduce Ibadi Islamic theology to students and scholars of Islam” (p. 4) – a task in which she succeeds admirably. Her book is primarily a translation of a theological primer and supplementary text, preceded by a short introduction on the origins and history of Ibadi Islam to orient the readers and prepare them ...